Rethinking Data Collection on Logistics Facilities: New Approach for Determining the Number and Spatial Distribution of Warehouses and Terminals in Metropolitan Areas. Issue 1 (January 2017) - Heitz, Adeline; Launay, Pierre; Beziat, Adrien
The aim of this paper is to propose a new methodology for collecting data on logistics facilities in urban regions. This methodology was used to build a database of warehouses and transport terminals in the Paris region for 2015, which added to the various existing databases by using open source data. The new and existing databases were compared so that the limitations of the latter could be considered, and preliminary conclusions were made about the distinctive characteristics of the new methodology. Then, the new database was used to study the spatial distribution of logistics facilities in the Paris region. Finally, a new typology of logistics facilities was proposed to characterize the different logistics sectors without relying on activity codes.